Um novo olhar : prática educomunicativa com a pinhole - Santos, Lidiane da Silva (2018)
The need to understand the processes of building a knowledge that allows a critical and reflective positioning proposed by the present leads to the search of new educational paths. Educommunication presents itself as one of these forms seeking to agglutinate educational and communicative dimensions. In the face of this reality, it is desired to develop a Guide to Pinhole Photography Workshops aimed at high school teachers. Starting from a bibliographical research, it searches for concepts and a history of image, photography, interpellation and education and pinhole. This technique was chosen for its simplicity in the production process, which facilitates an understanding of the learners about the basic and primordial photographic processes of photography. It is believed that when one understands the path taken for the development of the technique, it allows a greater understanding about the photographic act and, consequently, causes a reflection about the look. With this understanding, the production of the Guide was based on the field research carried out with high school students aged between 16 and 18 years old from the city of Montes Claros, Minas Gerais. All subjects were students enrolled in a private school in the city. The choice of the school was due to the scope of the same that embraces students from other cities and with a variation in social stratification. The subjects that participated in the research already had a certain involvement with the photographic reality, which served as the criterion of choice. In view of the preparation of the Guide, it was tested the realization of a previously organized pinhole workshop, which served as a study laboratory. For the evaluation of the method used in the pilot workshop, an in-depth interview was used as well as the digital recording (video and audio) of the meetings. The evaluation of the participants, as well as the result of their practical productions allowed the preparation of the Guide. This product considers the educomunicative bases and with the increase of the perception of the participants was structured in order to correspond with the intention to favor a better understanding of the practice thus allowing a critical development in front of the images. The scripts presented in the Guide are in accordance with the responses obtained during and after the workshops. We emphasize the subjects' perception of the need to work more effectively with the knowledge not only of photographic techniques, but with the understanding of the process and the extension of the same to an experience and critical understanding of the use and production of images.